Features of using hops and CO2-extract in brewing - Protsenko, Lidia; Litvynchuk (Vorontsova), Svitlana (My University, 2017)
Aromatic hop with a low alpha-acid content can be used in brewing as a polyphenol additive in combination with a CO2-extract, taking into account the quantitative content and qualitative composition of hop products and adhering to a certain technology of making beer.
Keywords: hop; СО2-extract; polyphenolic compounds; beer; хміль; СО2-екстракт; поліфеноли; пиво; хмель; СО2-экстракт; полифенолы; кафедра фізики та професійної безпеки